Planning Subways By Tunnel Or Cut-And-Cover-- Some Cost-Benefit Comparisons - Richard J. Proctor; George A. Hoffman (Society for Mining, Metallurgy & Exploration, 1974)
INTRODUCTION We will discuss here only the subway construction phase; that is, two to five years at a given location--not the long-term analysis. We also will compare some tunnel construction methods used for BART and in Los Angeles. Typically, urban planners and engineers try to balance a new mass transit system to include tunneled subways, cut-and-cover construction in city streets, and elevated guideways. Their decisions are based on many factors, most of which can be quantified. But there are some socio-economic-environmental factors which are almost intangible, or nonquantifiable, and these are rarely included in the final report for a rapid transit system. There are two reasons for this: First, it is difficult to evaluate disruptions and psychological inconveniences to individuals and to the community during the construction period, and even more difficult to assign costs because the valuations are always subjective. Second, the rapid transit project capital costs are given in the final report and the public knows them; but the intangible social costs are borne by the affected neighborhood community, not the entire city, and as such they are "hidden costs," which in fact may add as much as 25 percent to the total system cost.